Comparison of the Methods of Graphical Solution of Symbolic Sensitivity - Brtník, Bohumil; Matoušek, David (IEEE (Institute of Electrical and Electronics Engineers), 2018)
Signal-flow graph (SFG) technique is a very useful tool for a hand analysis of a small and medium-size networks and/or subnetworks of large systems. Last days, the SFG's have been effectively used for the sensitivity solutions, too. This paper describes the comparison between two graph methods for derivation transfer function: the nullor modified Coates flow graph symbolic analysis and the transformation graphs for symbolic analysis. As is given, in some cases the transformation graphs are more useful thanks to their clarity than standard solving methods.
Porovnání metod grafického řešení citlivosti
Keywords: nullor model; modified Coates graph; transformation graph; sensitivity analysis; nulorový model; modifikovaný Coatesův graf; transformační graf; citlivostní analýza